2021
DOI: 10.1101/2021.02.03.21251054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related heterogeneity in immune responses to SARS-CoV-2 vaccine BNT162b2

Abstract: Vaccines remain the cornerstone for containing the SARS-CoV-2 pandemic. mRNA vaccines provide protection in clinical trials using a two-dose approach, separated by a three-week gap. Here we assessed real world immune responses following vaccination with mRNA-based vaccine BNT162b2. Following the first and second doses of the BNT162b2 vaccine, we measured IFNgamma; T cell responses, both total IgG Spike, IgG Spike RBD and neutralising antibody responses to Spike in sera using a lentiviral pseudotyping system. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
117
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 61 publications
21
117
5
1
Order By: Relevance
“…Although the evidence on single-dose immunogenicity of BNT162b2 in older adults is mixed, [28][29][30] pooled data from four ChAdOx1 trials, including over 950 participants aged 70 years and older, indicated vaccine effectiveness of 63•9% (95% CI 46-75•9) against all infection at 22-90 days after a single dose, 17 which is in line with our findings. Our estimates of vaccine effectiveness against all infection are not dissimilar to those from phase 3 efficacy testing of the single-dose Ad26.COV2.S vaccine (Janssen), which was 67•9% (95% CI 38•2-82•8) effective against symptomatic COVID-19 at 28 days or more after vaccination in those aged 60 years and older.…”
Section: Chadox1 Bnt162b2supporting
confidence: 88%
“…Although the evidence on single-dose immunogenicity of BNT162b2 in older adults is mixed, [28][29][30] pooled data from four ChAdOx1 trials, including over 950 participants aged 70 years and older, indicated vaccine effectiveness of 63•9% (95% CI 46-75•9) against all infection at 22-90 days after a single dose, 17 which is in line with our findings. Our estimates of vaccine effectiveness against all infection are not dissimilar to those from phase 3 efficacy testing of the single-dose Ad26.COV2.S vaccine (Janssen), which was 67•9% (95% CI 38•2-82•8) effective against symptomatic COVID-19 at 28 days or more after vaccination in those aged 60 years and older.…”
Section: Chadox1 Bnt162b2supporting
confidence: 88%
“…Anti-N IgG antibodies are known to have a shorter half-life than anti-S1 IgG antibodies, therefore individuals who were anti-S1 IgG-positive but anti-N IgG-negative might have had an older exposure to SARS-CoV-2 (preprint). 9 Anti-S1 IgG antibody concentrations were compared between timepoint 1 and timepoint 2 within seropositive and seronegative groups.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Likewise, suboptimal vaccine efficacy has been reported in older and immunocompromised populations. [9][10][11][12] The prospect that patients with cancer might be wholly or partially unprotected by vaccination has implications for their health and for the control of SARS-CoV-2 transmission within their environments, including health-care facilities. 7,13,14 Consequently, we launched the SOAP-02 vaccine study to address the safety and efficacy of the BNT162b2 vaccine in patients with cancer, and to investigate whether or not a boost at day 21 following initial vaccination was beneficial in this patient population.…”
Section: Introductionmentioning
confidence: 99%